Comparative proteomics of ovaries elucidated the potential targets related to ovine prolificacy - Li, Chunyan; Zhou, Mei; He, Xiaoyun; Di, Ran; Zhang, Zijun; Ren, Chunhuan; Liu, Qiuyue; Chu, Mingxing (Frontiers in Veterinary Science, 2023)
Small Tail Han (STH) sheep, a unique Chinese breed, is recognized for its early maturity, year-round estrus and prolificacy. However, the molecular mechanism of its high prolificacy has not been fully elucidated. Proteomics approach is feasible and effective to reveal the proteins involved in complex physiological processes of any organism. Give this, we performed the protein expression profiling of ovarian tissues during the luteal phase using polytocous STH sheep (litter size ≥2, three consecutive lambings) and monotocous STH sheep (litter size =1, three consecutive lambings) (PL vs. ML), the follicular phase using polytocous STH sheep (litter size ≥2, three consecutive lambings) and monotocous STH sheep (litter size =1, three consecutive lambings) (PF vs. MF), respectively. Parallel Reaction Monitoring (PRM) was conducted to validate the differentially abundant proteins (DAPs). The tandem mass tag (TMT) quantitative proteomic results showed that a total of 5,237 proteins were identified, of which 49 and 44 showed differential abundance in PL vs. ML and PF vs. MF groups, respectively. Enrichments analyses indicated that the DAPs including TIA1 cytotoxic granule associated RNA binding protein like 1 (TIAL1), nicotinamide phosphoribosyltransferase (NAMPT), cellular retinoic acid binding protein 1 (CRABP1) enriched at luteal phase, while TIAL1, inhibin beta-a-subunit (A2ICA4), W5PG55 enriched at follicular phase potentially mediated reproductive processes in polytocous ewes. Furthmore, six DAPs were verified using PRM, confirming the accuracy of the TMT data acquired in this study. Together, our work expanded the database of indigenous sheep breeds and provided new ovarian candidate molecular targets, which will help studying the genetic mechanisms of ovine prolificacy.